2012
DOI: 10.1016/j.reseneeco.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbines and coastal recreation demand

Abstract: We examine the impact of coastal wind turbines on local coastal tourism and recreation for residents of the northeastern coastal counties in North Carolina. A combination of telephone and web survey data are used to assess the impact of coastal wind farms on trip behavior and site choice. Most of the respondents to our telephone survey claim to support offshore wind energy development, and independent survey data suggest that the observed levels of support may be indicative of the broader population in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 22 publications
5
51
2
Order By: Relevance
“…Tourism expenditures have been found to be directly linked with family incomes (Abbruzzo, Brida, & Scuderi, 2014). Similar to our findings, previous studies have also identified household income to have a positive impact on recreational behaviour (Landry, Allen, Cherry, & Whitehead, 2012). Visitors (mostly foreigners) with high income may be willing to pay more if the recreational quality of a park improves.…”
Section: Discussionsupporting
confidence: 86%
“…Tourism expenditures have been found to be directly linked with family incomes (Abbruzzo, Brida, & Scuderi, 2014). Similar to our findings, previous studies have also identified household income to have a positive impact on recreational behaviour (Landry, Allen, Cherry, & Whitehead, 2012). Visitors (mostly foreigners) with high income may be willing to pay more if the recreational quality of a park improves.…”
Section: Discussionsupporting
confidence: 86%
“…Landry et al [30] was one of the few recreational demand studies to estimate SP and changes in future beach visitation (n = 118) given an offshore wind farm was built adjacent to North Carolina beaches (USA). A spatial attribute for distance was included in the CE, prompting respondents to choose their trip at a site-generic beach with a wind farm located either in the Atlantic Ocean or in inland, sound waters.…”
Section: Landry Et Almentioning
confidence: 99%
“…Following Landry et al [30], Westerberg et al [28] examined offshore wind development impacts using a coastal, recreational demand model in the Languedoc Roussillion region of the French Mediterranean. The authors estimated WTP and WTA for coastal recreation, defined in the payment vehicle as a change in the accommodation price, near a proposed 108 MW offshore wind project (consisting of 30 × 3.6 MW turbines, typically 80 m nacelle and 55.5 m blades =133.5 m total) using an explicit distance attribute at five, eight or twelve km from shore.…”
Section: Westerberg Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates from California produced with site choice models are of a similar magnitude, $27 to $29 per household (Lew and Larson 2009). Seasonal value estimates range from $68 per household (Rehobeth, DE;von Haefen, Phaneuf, and Parsons 2004) to $1,104 per household (all NC beaches; Landry et al 2010). Lew and Larson (2009) over a two-month period in San Diego, California at around $1,700 per household.…”
Section: Beach Visitorsmentioning
confidence: 99%